The congested International Match Calendar in football: views of 1055 professional male players - Pillay, L.; Burgess, D.; van Rensburg, D. C.; Kerkhoffs, G. M.; Gouttebarge, V. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background The International Match Calendar congestion affects players recovery. The views of a worldwide cohort of professional football players is shared in this communication.